Errors and Difficulties Faced During the Elaboration of Undergraduate and Graduate Thesis by Peruvian Students: Pedagogical Implications - Perdomo, Bexi (2022)
Objectives. To describe mistakes students made and difficulties they reported in the process of elaborating their degree work. Methodology. Documentary design research was conducted. It included a sample of theses (n = 120) submitted to obtain academic degrees between 2018 and 2019. Information was sought on errors of substance (unity, demonstration, and depth) and form (presentation, writing and spelling, use of standards for the inclusion of citations and bibliographic references, and text structure). As part of data triangulation, some authors of these theses were interviewed to learn about the difficulties they faced during the writing process. A qualitative content analysis matrix, a checklist, and Zoom interviews with the authors of the theses were used. This methodological triangulation of data allowed a complete vision of the study problems. Results. Errors of substance and form were recorded in high percentages for both undergraduate and graduate theses. Among the substantive errors, those associated with failures when writing results and discussion (>80%) and those associated with spelling errors and the use of the reference system (100%) stand out. Concerning the difficulties, those associated with the advising, the thesis advisor, and the thesis were appreciated. Of all these difficulties, the most frequent ones were the performance of statistical analysis (100%) and disagreements between tutor and jurors (95%). Undergraduate and graduate thesis writers make similar errors and experience similar difficulties in their elaboration process. Conclusions. Form and substance errors are frequent, including misuse of the reference system and mistakes of a methodological nature. Undergraduate and graduate thesis writers face difficulties related to poor training on methodology and writing of scientific texts. Besides, they suffered from a lack of concordance of criteria between tutors and evaluators.